2018
DOI: 10.29185/hayuretim.469862
|View full text |Cite
|
Sign up to set email alerts
|

Karma Yeme İlave Edilen Probiyotik, Prebiyotik ve Enzim Karışımının Etlik Piliçlerde Performans, Karkas, Organlar, İleal pH ve Viskozitesi Üzerine Etkileri

Abstract: Objective:The experiment was conducted to determine the individual and combined effects of probiotic, prebiotic and enzyme on performance, carcase, organs, intestinal pH and viscosity of broilers. Material and Methods: A total of seven hundred day-old male Ross-308 broiler chicks were individually weighted and distributed into 28 floor pens with 25 chicks per pen in from 0 to 42 d of age. Seven starter and grower diets were formulated to provide a similar nutrient profile with the exception of using experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
3
10
1
Order By: Relevance
“…In another study conducted, the effect of probiotic and enzyme addition on mixed feed was found to be significant on ileal pH. The highest ileal pH was found in the control group (Kırkpınar et al, 2018). The excessive buffering action of ileum was not observed in broilers, given either 0.5% or 1.0% of the additive in the current study.…”
Section: Ph Values Of Intestinal Segments Of Broilerssupporting
confidence: 42%
“…In another study conducted, the effect of probiotic and enzyme addition on mixed feed was found to be significant on ileal pH. The highest ileal pH was found in the control group (Kırkpınar et al, 2018). The excessive buffering action of ileum was not observed in broilers, given either 0.5% or 1.0% of the additive in the current study.…”
Section: Ph Values Of Intestinal Segments Of Broilerssupporting
confidence: 42%
“…(2009) [ 27 ], who reported supplementation of probiotic and prebiotic combination improved the final body weight of broilers at 42 d of age. Similarly, supplementation of probiotic + prebiotic and probiotic + enzyme combination increased the body weight of broilers compared to control at 42 d of age [ 9 ]. Barad et al .…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation activity of inulin inhibits the growth of harmful strains, selectively stimulates the growth of beneficial bacteria by decreasing the intestinal pH through increasing the absorption of short chain fatty acids and thus promotes the growth of broiler chickens [ 7 , 8 ]. Similarly, probiotic + prebiotic supplementation decreased intestinal pH and viscosity in broilers [ 9 ]. Addition of probiotics ( Lactobacillus acidophilus and lactose fermenting enterobacteria) and prebiotic combinations in broilers significantly (P<0.05) increased the villus height and crypt depth of the duodenum, ileum and jejunum [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that using acidifiers and probiotics in combination had a greater impact on broiler production and health than using an acidifier and probiotic separately [ 2 ]. In addition, several studies have reported that combining probiotics with prebiotics increased probiotic efficacy compared with using probiotics alone [ 6 , 7 ]. Wheat bran has been identified as a prebiotic-rich and affordable feed ingredient for broiler chickens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%